2022
DOI: 10.3390/nu14214590
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Functional Constipation among Students of a Chinese University: A Cross-Sectional Study

Abstract: Functional constipation (FC) is prevalent worldwide and is an increasingly prominent problem among university students. However, there is a paucity of research on FC in university students. This study aimed to assess the prevalence of FC among Chinese university students by the Rome III criteria and investigate its associated factors. This cross-sectional study was conducted by online questionnaires among 929 university students at a Chinese university. Food consumption was assessed with the Semi-Quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
1
1
Order By: Relevance
“…Based on Rome criteria, another recent systematic review and meta-analysis found that pooled prevalence of CC was 15.3% using Rome I, 11.2% using Rome II, 11.4% using Rome III, and 10.1% using Rome IV ( 7 ). Previous studies on college and university students in China and Tunisia reported that the prevalence of CC ranged from 5.1 to 11.4%, which was lower than our finding ( 20 22 ). However, a higher prevalence (23.9%) of CC was found in the Australian adult population ( 23 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Based on Rome criteria, another recent systematic review and meta-analysis found that pooled prevalence of CC was 15.3% using Rome I, 11.2% using Rome II, 11.4% using Rome III, and 10.1% using Rome IV ( 7 ). Previous studies on college and university students in China and Tunisia reported that the prevalence of CC ranged from 5.1 to 11.4%, which was lower than our finding ( 20 22 ). However, a higher prevalence (23.9%) of CC was found in the Australian adult population ( 23 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Eighteen variables were included as potential predictors in the current investigation. The predictors were developed using many published studies on FC in young people or college-bound students [19,22]. Age, BMI, and the ve criteria for the ROME-III categorization of FC (the last two were taken because the question of "Manual maneuvers on > 25% of defecations" received no response and was therefore removed from the data set) Too-small bowel movement frequency, bleeding or tearing in the colon during or following a bowel movement, abdominal pain and discomfort, Bristol's Scale of Stool Consistency, Exercise Frequency: "Do you exercise?"…”
Section: Selection Of Predictorsmentioning
confidence: 99%